Love and Moral Psychology in Global Politics: A Kantian Reworking of Rawls and Nussbaum - Rinne, Pärttyli (Con-Textos Kantianos. International Journal of Philosophy, 2020)
For both John Rawls and Martha Nussbaum, the concept of love plays a significant role in moral psychology. Rawls views the sense of justice as grounded in parental love, and continuous with love of mankind. Nussbaum’s recent defence of patriotism revives the emotion of love as essential for political contexts. I argue that love ought to play a substantial part in the shaping of global politics, and that a moral psychology of love based merely on a combination of Rawls’s and Nussbaum’s accounts fails to produce an adequate ground for conceptualizing moral motivation with respect to addressing transnational concerns of justice. I contend that by critically synthesizing Rawls’s and Nussbaum’s conceptions of love and moral psychology with resources from Kant’s ethics, it is possible to develop a more attractive, and potentially politically effective, conception of love of human beings in the framework of political liberalism.
Keywords: love; moral psychology; Rawls; Nussbaum; Kant; political liberalism